The predicate stable combinations of words in the scientific humanitarian text - Юмачікова, Олена Михайлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In the proposed study, an attempt was made, based on the works of domestic and foreign linguists, to analyze predicate steady combinations of words in the scientific humanitarian text. The stable combinations of words that fulfill the role of predicates of action, state, process and quality in a semantic-syntactic sentence structure are considered and systematized. In the course of the study, it was established that predicate stable combinations of words used in the Ukrainian-language scientific humanitarian text perform in the semantic-syntactic sentence structure the role of predicates of action, state, process or quality, and through this semantic unity form a special class of predicates. Investigated predicate steady combinations of words in the scientific humanitarian text become standard, immanent feature of style and become the nature of constantly used forms of expression, which gives grounds to call them one of the important means of standardizing the text variety.